TO EVALUATE THE OUTCOMES OF TOTAL HIP ARTHROPLASTY USING THE SUPERPATH APPROACH AT VIET DUC UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: To evaluate the outcomes of total hip arthroplasty using the SuperPATH approach at Viet Duc University Hospital.Methods: A prospective descriptive cross-sectional study was conducted on 40 patients who underwent total hip arthroplasty via the SuperPATH approach at Viet Duc University Hospital between January 2025 and December 2025.Results: The mean age of the patients was 51.8 ± 8 years, with a male-to-female ratio of 4/1. The mean operative time was 64.2 minutes, mean incision length 7.93 ± 1.42 cm, mean intraoperative blood loss 312 ± 49,2 ml, and mean hospital stay 5.6 ± 1.04 days. Significant improvements were observed postoperatively: flexion increased from 92.54° to 119.30°, abduction from 21.30° to 33.61°, adduction from 15.75° to 22.88°, and external rotation from 22.50° to 28.75°. The mean HHS improved significantly from 45.1 ± 5.38 preoperatively to 89.95 ± 3.2 postoperatively.Conclusion: Total hip arthroplasty via the SuperPATH approach demonstrated favorable outcomes, with good postoperative functional recovery, minimal blood loss, short hospital stay, and low rates of complications and dislocation.
Keywords: SuperPATH approach, total hip arthroplasty, minimally invasive surgery.